Do environmental pollutants increase obesity risk in humans?. (5th October 2016) - Wang, Y.; Hollis‐Hansen, K.; Ren, X.; Qiu, Y.; Qu, W.
Summary: Objectives: Obesity has become a global epidemic and threat to public health. A good understanding of the causes can help attenuate the risk and spread. Environmental pollutants may have contributed to the rising global obesity rates. Some research reported associations between chemical pollutants and obesity, but findings are mixed. This study systematically examined associations between chemical pollutants and obesity in human subjects. Methods: Systematic review of relevant studies published between 1 January 1995 and 1 June 2016 by searching PubMed and MEDLINE®. Results: Thirty‐five cross‐sectional ( n  = 17) and cohort studies ( n  = 18) were identified that reported on associations between pollutants and obesity measures. Of them, 16 studies (45.71%) reported a positive association; none reported a sole inverse association; three (8.57%) reported a null association only; six (17.14%) reported both a positive and null association; seven (20.00%) reported a positive and inverse association; and three studies (8.57%) reported all associations (positive, inverse and null). Most studies examined the association between multiple different pollutants, different levels of concentration and in subsamples, which results in mixed results. Thirty‐three studies reported at least one positive association between obesity and chemicals, such as polychlorinated biphenyls, biphenyl A, dichlorodiphenyltrichloroethane, dichlorodiphenyldichloroethylene and more. Certain chemicals, such as biphenyl A, were more likely to have high ORs ranging from 1.0 to 3.0, whereas highly chlorinated polychlorinated biphenyls were more likely to have negative ORs. Effects of chemicals on the endocrine system and obesity might vary by substance, exposure level, measure of adiposity and subject characteristics (e.g. sex and age). Conclusions: Accumulated evidences show positive associations between pollutants and obesity in humans. Future large, long‐term, follow‐up studies are needed to assess impact of chemical pollutants on obesity risk and related mechanisms.